TÜBİTAK 4006 Bilim Fuarlarının Öğretmenler* ve Öğrenciler** Açısından Değerlendirilmesi: Polatlı Örneği. - Yener, Dündar; Balcı, Ebru (Electronic Turkish Studies, 2020)
In recent studies, it emphasizes the importance of learning environments in which students actively participate. Because it is seen that students learn information more meaningfully in the environments in which they actively participate. In this context, the importance of science fairs in which students take an active role has also increased. In order to examine the effects of students on their achievements, attitudes, and perceptions of science lessons, it is necessary to conduct studies and follow up on science fairs. For this reason, it is aimed to examine the perspectives of the teachers who have various categories in their structure, appeal to all individuals, large and small, and who work as organizers and participants in the TUBITAK 4006 Science Fairs Support Program and students working in these fairs. This study, which was conducted to examine the opinions of teachers and students about science fairs, was carried out as a case study from qualitative research patterns. Structured interview form was used to collect data in the study. The study was carried out with 10 educational institutions that held TUBITAK 4006 Science Fair in Polatlı district center in 2016-2017 academic year. The participants of the study consisted of 60 teachers (35 females and 25 males) and 352 students (167 females and 185 males) who were working in science fairs. The following findings and results were obtained in the analysis of the data. One of the main reasons for teachers to participate in science fairs is to share their experiences with other people and educate conscious students. In addition, teachers stated that they would be useful for their resumes in science fairs. The participants stated that they have benefited from the past works when choosing the projects to take place in the fair. This is followed by the work of the students who will take part in the fair. When choosing the students to participate in science fairs, the participants stated that they pay attention to volunteering, interest in fairs, academic achievements and whether they have participated in science fairs before. In addition, the fact that science fairs are a useful activity, directing them to scientific studies and providing students with increased knowledge has been determined as the positive aspect of the fairs. However, they stated that the project budget was inadequate, reporting was difficult and demanding intensive work as a negative aspect. In addition, a few of the participants stated that the organization of the science fair was requested and required by the administration. The reason why students participate in science fairs is the fact that the fairs are fun, the sense of accomplishment and learning new things come to the fore. While the students were researching the projects they wanted to take place in the fair, they stated that they focused on the topics they heard in general. However, while researching the projects, it was determined that male students mostly use sources such as scientific journals and books, although most of the students get help from related institutions and organizations. The students who participated in the study generally stated the positive aspect of science fairs as contributing to academic success and offering solutions to the problems encountered. On the other hand, female students expressed the problems encountered in the implementation of SPS as a negative aspect, while male students expressed the lack of communication with the teacher as a negative aspect.